Epidemiological surveillance of enteric viral diseases using wastewater in Africa - A rapid review - Tafadzwa Dzinamarira; Gashema Pierre; Patrick Gad Iradukunda; Nigel Tungwarara; Solomon Mukwenha; Etienne Mpabuka; Kidson Mataruka; Itai Chitungo; Godfrey Musuka; Grant Murewanhema (Elsevier, 2022)
Viral enteric pathogens remain an important cause of diarrhoeal outbreaks among children in sub-Saharan Africa (SSA). Consequently, diarrhoeal illness remains a significant cause of morbidity and mortality in the under-fives in SSA. These outbreaks associated with viral pathogens tend to be seasonal and early warning systems for impending outbreaks could be very crucial for triggering preventive public health response and building public health resilience to deal with increased demand for medical services. Wastewater surveillance for pathogens is an important epidemiological component that could inform early warning systems. The objective of this rapid review was to evaluate the use of wastewater for epidemiology surveillance of enteric viral pathogens. Nine studies met the inclusion criteria. Eight viral pathogens were reviewed and analysed from 6 countries that performed wastewater analysis. Six studies explored the epidemiologic significance of viral pathogens in wastewater. The findings of this review revealed that monitoring of wastewater can provide an additional tool to determine the epidemiology of viral pathogens circulating in the community thereby providing early warning of potential outbreaks using wastewater-based epidemiology methods. Five of the included studies revealed the occurrence of viral pathogens in raw sewage and treated wastewater as an indication of inefficient elimination of viruses leading to potential release into water sources which presents a public health risk, increasing the risk of inducing gastroenteritis in the population. Six studies revealed the need for public health authorities to realise the potential benefit of environmental surveillance (ES) as an additional tool to determine the epidemiology of viral pathogens circulating in each community. Despite the significant public health challenge associated with enteric viral pathogens in sub-Saharan Africa, there remains remarkable underinvestment in potentially epidemiologically beneficial research, including wastewater-based epidemiology for these infections.